Pelatihan Cara Berbahasa Indonesia yang Benar kepada Mahasiswi Autis di Jurusan Pendidikan Khusus FIP UNM - Abdul Hadis; Wizerti Ariastuti Saleh; Nurhayati B; Besse Qur'ani (JKM: Jurnal Kemitraan Masyarakat, 2025)
There are quite a number of students with special needs in various types of disorders who have the competence to be independent in society. However, the attention of families, schools, communities, and the government to empower them is still lacking, including the attention of parents and the government regarding the importance of training students with special needs for all types of disabilities (including autistic female students) to be able to speak Indonesian correctly through training activities on how to speak Indonesian correctly is also still lacking. Therefore, the main objective of this activity is to provide training activities on how to speak Indonesian correctly to female students with autism so that they can speak Indonesian correctly. The method used in this community service is through counselling, training, and experimentation. The main finding of this community service, namely autistic female students with one autistic child as the subject, if trained to speak Indonesian correctly, can communicate socially in Indonesian, so this activity is beneficial in improving social communication skills in correct Indonesian for autistic female students. In conclusion, the implementation of training in the correct use of Indonesian language for autistic female students is a new and urgent finding, as it addresses the difficulties faced by these autistic female students in communicating socially using Indonesian.